Design of a Local Server-Based Student Data Collection System at Salafiyah Syafi’iyah Sukorejo Islamic Boarding School - Sariratul Aisyah; Fitri, Nurdiana; A. Hamdani (Yayasan Kita Menulis, 2026)
Management of dormitory room data in Islamic boarding schools is still carried out manually by recording information in notebooks. This approach has the potential to cause data duplication, inaccuracies in record-keeping, loss of students' room placement history, and slow data retrieval processes. This study focuses on designing a dormitory room data management information system based on a local server, without including the implementation stage. The research methods include requirements analysis, system modeling using Unified Modeling Language (UML), and user interface design. The result of this study is a complete and structured system design that can be used as a reference for system development and implementation at a later stage.